Acceptance model of SaaS cloud computing at northern Malaysian main campus public universities - Al-Madhagy, Taufiq Hail Ghilan (2018)
Technology advancement has side effects, although it has moved in a fast pace that facilitated life and increased business revenue. To cope with negative aspects while looking for friendly technology, Software as a Service (SaaS) Cloud Computing emerged to preserve natural resources, effectively utilize computing and power consumption, while achieving performance, decreasing cost, and increasing revenue. Yet, there are paucity in empirical studies investigating salient factors affecting the usage, acceptance, or adoption of SaaS services from the individual perspectives specifically in higher education sector. The main objective of this study is to investigate the salient factors with proper model that includes technical, social and control characteristics, as well as user security predisposition. Besides, educational level has also proven to be influential in adopting innovations. Hence, probing its role is another objective. The last objective is to investigate differences between student and lecturer groups in the relationships postulated in the model. A survey with questionnaires was conducted on students and lecturers in four public universities in Northern Malaysia. The scope of the acceptance is to investigate the personal-level use of SaaS services. Decomposed Theory of Planned Behaviour (DTPB) and Diffusion of Innovation Theory (DOI) were applied. Results revealed appropriateness of the model although the role of Trialability and Subjective Norms were not significance. The findings contribute to the body of knowledge and literature in highlighting the role of these factors that SaaS providers could benefit in planning for new services and in promoting SaaS usage to universities.